2004
DOI: 10.1159/000081320
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Hyperfractionated Radiation Therapy with Protracted 5-Fluorouracil Infusion in Patients with Locally Advanced Pancreatic Cancer

Abstract: Objective: This study investigated the maximum-tolerated dose of hyperfractionated radiation therapy with protracted 5-fluorouracil (5-FU) infusion in patients with locally advanced, unresectable pancreatic cancer. Methods: Five cohorts of patients were scheduled to receive escalating doses of hyperfractionated radiation therapy (range, 45.6–64.8 Gy). All patients received two fractions of 1.2 Gy each (separated by 6 h) per day for 5 days a week, and received protracted 5-FU infusion (200 mg/m2/day)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In addition to lung cancer, a large number of phase I RT trials (n = 17) were performed to improve the treatment of brain (n = 4) [28][29][30][31][32], pancreas (n = 7) [33][34][35][36][37][38][39] and prostate cancers (n = 6) [40][41][42][43][44][45][46][47] (for details per study see Appendix 3). The majority of these studies (n = 11, 65% [29,30,[33][34][35]39,40,42,43,45,46]) re- ported only safety and toxicity data. In general, the trials were performed as multicentre studies (n = 10, 59%) [28,29,[31][32][33][34][35][36]38,43] in the Northern America (n = 12, 71%) [28][29][30][33][34][35][36]…”
Section: Brain Prostate and Pancreatic Carcinomasmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to lung cancer, a large number of phase I RT trials (n = 17) were performed to improve the treatment of brain (n = 4) [28][29][30][31][32], pancreas (n = 7) [33][34][35][36][37][38][39] and prostate cancers (n = 6) [40][41][42][43][44][45][46][47] (for details per study see Appendix 3). The majority of these studies (n = 11, 65% [29,30,[33][34][35]39,40,42,43,45,46]) re- ported only safety and toxicity data. In general, the trials were performed as multicentre studies (n = 10, 59%) [28,29,[31][32][33][34][35][36]38,43] in the Northern America (n = 12, 71%) [28][29][30][33][34][35][36]…”
Section: Brain Prostate and Pancreatic Carcinomasmentioning
confidence: 99%
“…In general, the trials were performed as multicentre studies (n = 10, 59%) [28,29,[31][32][33][34][35][36]38,43] in the Northern America (n = 12, 71%) [28][29][30][33][34][35][36][37]40,[44][45][46][47][48] (Table 1). Seven (41%) used the modified Fibonacci design for RT dose escalation [30,33,34,[37][38][39]41]; in the other ten (59%) no specific design was used [28,29,31,32,35,36,40,42,43,45,46]. Dose escalation was performed in nine of these studies by increasing the number of fractions (53%) [31,34,36,38,39,41,43,…”
Section: Brain Prostate and Pancreatic Carcinomasmentioning
confidence: 99%
See 2 more Smart Citations
“…The median survival was 12.2 months and the 1-year survival rate was 55.0%. The authors concluded that the toxicity was tolerable up to a dose of 64.8 Gy and conducted a phase II study testing this regimen [27].…”
Section: Definitive Chemoradiotherapy In Unresectable Pancreaticmentioning
confidence: 99%